Eduardo Reyes: www.tallersur.cl - Reyes, Eduardo (Base Diseño e Innovación, 2015)
The handicrafts in copper developed in Chile, such as the etched and the enameling, are not known in other coun-tries where Chile has participated as an invited to inter-national fairs. I have noticed this in Spain, other parts of Europe, the United States, Central America and Latin America. That is to say, in commercial terms, “I have had no competition”. I have known the chiselling of India, in Mexico an extraordinary job of forging and hammering in Santa Clara, glazing in the United States, and powdering in Argentina and Uruguay.In Chile, before the coup d’état of 1973, craftsmen such as Raul Celery, Juan Reyes and Alicia Cáceres, marked working lines of embossing, (hammering) giving forms and volumes of very elaborated colonial type metalwork.As a consequence of the resulting political situation, many artists and academics associated with the arts joined the activity as a means of subsistence. This is what happe-ned with Luis Araneda, Vanessa Ingles, Mario Vásquez and Arturo de la O, among others. All of them installed a new artistic dimension applying their knowledge, aesthetic and technical concepts, which marked a qualitative leap in the work of copper, transforming it in the main “urban craft” of the country in the 1970s and 1980s.